Utility of 99mTechnetium Pertechnetate Thyroid Scan and Uptake in Thyrotoxic Patients: Jordanian Experience - Al-Muqbel, Kusai M. (World Journal of Nuclear Medicine, 2022)
Objective The objective of this study was to assess our local experience with 99mTechnitium thyroid uptake (TcTU) in thyrotoxicosis by examining mean and range of TcTU in both euthyroid patients and thyrotoxic patients. We also wanted to see how well TcTU performed as a substitute for radioiodine thyroid uptake in thyrotoxicosis.Methods The medical records of thyrotoxic patients were reviewed retrospectively. Inclusion criteria were: (1) thyrotoxicosis was proven biochemically, (2) the patient underwent TcTU at the time of thyrotoxicosis diagnosis, (3) at least 6 months of follow-up, and (4) the final diagnosis was documented. All TcTU of euthyroid patients were also reviewed to determine local normal TcTU mean and range. Patients were divided into three groups: Graves' disease, toxic nodular goiter, and subacute thyroiditis. Each patient group's TcTU mean and range were assessed separately.Results There were 209 patients in total (54 euthyroid, 112 Graves' disease, 26 toxic nodules, and 17 patients with subacute thyroiditis). TcTU mean±standard deviation and range for euthyroid patients were 1.5±1.1% and 0.17 to 4.8%, 10.6±10% and 0.43 to 40% for Graves' disease, 4.5±4% and 0.6 to 15% for toxic nodules, and 0.5±0.4% and 0.18 to 1% for subacute thyroiditis. Although one-third of thyrotoxic patients' TcTU values overlapped with the normal TcTU range, the diagnosis was made using qualitative image analysis. Subacute thyroiditis was characterized by poor thyroid visualization, whereas Graves'/toxic nodular goiter was well visualized.Conclusion The mean and range of our local normal TcTU were similar to those previously published. TcTU was a useful alternative to radioiodine in the evaluation of thyrotoxicosis. About two-thirds of the patients had accurate test results. The diagnosis was reached in the remaining one-third of patients by combining quantitative and qualitative image features. This method allowed us to stop giving radioiodine to our patients, resulting in a significant reduction in patient radiation exposure.
Keywords: thyroid uptake; technetium-99m; thyrotoxicosis; radioiodine; Graves' disease; toxic nodular goiter